THE EFFECT OF PROGRESSIVE MUSCLE RELAXATION ON REDUCING STRESS AND BLOOD SUGAR IN TYPE 2 DIABETES MELLITUS PATIENTS IN THE WORK AREA OF TANIWEL PUBLIC HEALTH CENTER - Wiwi Rumaolat; Windarti Rumaolat; Mohammad Dahlan Sely (Lembaga Pengembangan Kinerja Dosen, 2022)
The main problems that often occur in people with Diabetes Mellitus (DM) are stress and an increase in blood sugar. Uncontrolled stress for a long time can lead to an increase in blood sugar levels, which can lead to various complications. One of the physical activities that can be done with relaxation is Progressive Muscle Relaxation (PMR) is an intervention that can be done in people with diabetes. The purpose of the study was to determine the effect of Progressive Muscle Relaxation (PMR) on increasing stress and blood sugar levels. The research design used a quasi-experimental approach with a pre-post-test control group design approach. The sample consisted of 36 respondents who were divided into 18 intervention groups and 18 control groups. The group was given a therapeutic intervention for 1 week with a duration of 2 times a day, namely in the morning and afternoon for 10-15 minutes. The instruments used are a glucometer, blood sugar level observation sheet, and Diabetes Distress Scale (DDS) questionnaire. Data analysis used the Wilcoxon test and Paired t-test to see pair data. Then for the research group, the data used the Man-Whitney Test. The results showed that there was a significant effect on decreasing blood pressure (p=0.013) and that there was an effect on decreasing blood sugar levels (p=0.034). Conclusion: Progressive Muscle Relaxation (PMR) affects reducing stress and blood sugar levels in Type 2 DM patients.